Early mathematical skill profiles of prematurely and full-term born children - Minna M. Hannula-Sormunen; Cristina E. Nanua; Eero Laakkonen; Petriina Munck; Noona Kiuru; Liisa Lehtonen; Pipari Study group (ELSEVIER SCIENCE BV, 2022)
Preterm birth is associated with low mathematical skills in children. This study on five-year-old Finnish children investigated whether mathematical skill profiles would differ between prematurely and full-term born children and how such profiles and other cognitive skills would be related. Mathematical skills included digit knowledge, spontaneous focusing on numerosity, arithmetic, counting and geometric skills. The investigated cognitive skills were phonological processing, working memory, instruction comprehension, speeded naming, inhibition and visuomotor skills. The participants were 119 preterm children with birth weight <1501 g and 100 full-term born children with normal birth weight. The results of latent profile analyses showed that preterm and full term born children differed in both number and shape of latent mathematical skill profiles,indicating quantitative and qualitative disparities. After controlling for birth weight or gestational age, maternal education, and other cognitive skills phonological processing, visuospatial working memory and speeded naming were uniquely associated with prematurely born children's five mathematical profiles. In full-term born children, only verbal working memory was related to their four mathematical profiles. (C) 2017 Elsevier Inc. All rights reserved.